Murder at Vinland [large type] - Maxwell, Alyssa (Maxwell, Alyssa. Gilded Newport mystery ;, 2024)
"August 1901: A fundraiser for a new Rhode Island Audubon Society brings Emma to Vinland, the Viking-themed seaside home of her relative, Florence Vanderbilt Twombly, where the guest of honor is Edith Roosevelt, wife of Vice President Theodore Roosevelt. Listening to the speakers and observing the ladies in attendance, Emma is struck by the contrast of the Viking warrior inspired elements in the house and the admirable but admittedly genteel cause of bird protection. Vinland bears the name of the Vikings' first landfall in North America, but in this room today there is most assuredly no one to fear. Emma's observation of harmless philanthropy is proven wrong the following morning when one of Mrs. Twombly's houseguests from the luncheon becomes mysteriously and dangerously ill. Accompanying police detective Jesse Whyte, Emma discovers a box of petit fours supposedly sent by Mrs. Roosevelt. They promptly rule out the Second Lady as a suspect, but someone has poisoned the cakes. Soon another box of desserts as well as letters tainted with ink containing caustic toxins show up at other grand Newport cottages. Are the ladies from the luncheon being targeted? Emma and Jesse must sort through possible motives and means because now more than the birds need protection . . ."--